Biologia de Semiaphis dauci (Fabricius, 1775) e Aulacorthum solani (Kaltenbach, 1843) (Hemiptera: Aphididae) associados à Arracacia xanthorrhiza (Bancroft, 1825) - Takada, Hélio Minoru (Universidade Federal de São Carlos, 2011)
The aphids are limiting for various crops, and in the case of the horticulture crops, it has been a problem for the cultivation of Arracacia xanthorrhiza (Bancroft, 1825), the arracacha. This plant, of Andean origin, has been well adapted to these climatic conditions of Southeast Brazil and conquered many consumers, currently representing an important food source due to its taste and nutritional value, thus providing a considerable income to small farmers. It is largely cultivated in the South and Southeast regions in Brazil. Although this culture is considered rustic, aphids has been causing great damage to its development. In the present work, the influence of temperature on the development of Semiaphis dauci (Fabricius, 1775) and Aulacorthum solani (Kaltenbach, 1843) was studied. The nymphal development period of S. dauci and A. solani on A. xanthorrhiza was of 23.84 and 33.02 days at 10 °C and 6.7 and 10.04 days at 25 °C, respectively. The minimum thermal threshold of development for the nymphal stage of 4.59 and 4.33 °C, the thermal constant 138.12 and 142.86 degrees-days and the approximate upper limit temperature ranged from 25 to 28 and 27 °C, respectively. The life table parameters indicated that temperatures of 22.5 and 25 °C provided the best thermal conditions for the S. dauci population growth, resulting the highest value of intrinsic rate of natural increase (rm=0.15), the lowest average value of the generation of 10.38 and 8.47 days and the shortest doubling times for the population with 4.74 and 4.55 days, respectively. The observed biological aspects indicate that A. solani has great potential for the population growth and a preference for smaller temperatures than S. dauci, and can be considered a potential pest for A. xanthorrhiza. The infestation of S. dauci in this species also causes severe damage to the plant, nevertheless other factors such as formation of dense colonies, lower mobility, and the action of toxins and viruses may also involved.
Semiaphis dauci (Fabricius, 1775) and Aulacorthum solani (Kaltenbach, 1843) (Hemiptera: Aphididae) associated with Arracacia xanthorrhiza (Bancroft, 1825)
Keywords: Ecologia; Batata baroa; Fecundidade; Pulgão; Temperatura; Pragas agrícolas - manejo integrado; Aphid; Arracacha; Temperature; Life table; Development; Degree-day; CIENCIAS BIOLOGICAS::ECOLOGIA